Power generation from a pH-regulated nanochannel through reverse electrodialysis: Effects of nanochannel shape and non-uniform H+ distribution. (20th January 2019) - Hsu, Jyh-Ping; Su, Tzu-Chiao; Lin, Chih-Yuan; Tseng, Shiojenn
Abstract: The power generated from the Gibbs free energy of mixing through reverse electrodialysis (RED) is a promising renewable energy of great potential. In this study the performance of a nanochannel having a pH-regulated surface in RED is examined, focusing on the influence of the bulk salt concentration, the distribution of H +, and the nanochannel size and its shape. Taking account of the effect of osmotic flow, we consider three types of nanochannel: bullet-shaped, conical, and trumpet-shaped nanochannels. Because the smaller the nanochannel space the more significant the degree of electric double layer overlapping the trumpet-shaped nanochannel has the best ion selectivity. As the ratio of (nanochannel length/curvature radius) varies the maximum power generated from a bullet-shaped nanochannel has a local maximum. This can be explained by the associated diffusion potential and the electric current passing through it. The results gathered provide desirable and necessary information for designing RED devices. In particular, the maximum power generation can be achieved by choosing appropriately the shape and the size of a nanochannel, and the bulk concentration ratio. Graphical abstract: